2005
DOI: 10.1097/01.prs.0000169701.16509.d6
|View full text |Cite
|
Sign up to set email alerts
|

5-Fluorouracil Selectively Inhibits Collagen Synthesis

Abstract: The clinical implication is that 5-fluorouracil could possibly reduce extracellular matrix production and therefore reduce recurrence of Dupuytren's disease of the hand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 35 publications
2
35
0
1
Order By: Relevance
“…Bulstrode et al [12] evaluated the effects of a single 5-minute exposure of different 5-FU concentrations on tendon fibroblasts and found that 5-FU caused a dose-dependent decrease in collagen synthesis, and this effect was maximal at a concentration of 25 mg/mL. Therefore, we used this concentration in the local treatment group.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Bulstrode et al [12] evaluated the effects of a single 5-minute exposure of different 5-FU concentrations on tendon fibroblasts and found that 5-FU caused a dose-dependent decrease in collagen synthesis, and this effect was maximal at a concentration of 25 mg/mL. Therefore, we used this concentration in the local treatment group.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies showed that a single dose of 5-FU is a very effective inhibitor of fibroblast proliferation and differentiation for prolonged periods [10,11]. The putative mechanism of 5-FU action, inhibition of thymidylate synthetase, and impairing function of nucleic acids would lead to a global inhibition of fibroblast function [12]. These observations have stimulated great interest in the potential benefits of this antimetabolite in fibrosis-related disorders.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In their in vitro study, Rayan et al found that Verapmil and Nifidipine inhibits myofibroblast contraction, and thus may be useful in the early stages of the disease [28]. The use of 5-Fluorouracil has been found, in vitro , to cause a dose-dependent selective and specific decrease in collagen production by inhibition of fibroblast proliferation and myofibroblast differentiation [59]. The authors concluded that the clinical implication is that 5-fluorouracil could possibly reduce the recurrence of Dupuytren's disease in the hand.…”
Section: Nonoperative Managementmentioning
confidence: 99%